‘We’ in English language textbooks for Japanese high school students - Gonja, Chika; Musaev, Talaibek (World Englishes, 2025)
In a globalised educational context, recognising English as an International Language is crucial for fostering cultural diversity in learning materials. This study examines the representation of ‘we’ in 24 government‐approved English textbooks for the course ‘English Communication I’, under Japan's 2018 national curriculum, aiming to understand the cultural and linguistic inclusivity portrayed. An analysis of 247 instances of ‘we’ associated with human characters revealed a pronounced bias towards ‘native’ English speakers, predominantly from the United States, while noticeably excluding ‘non‐native’ speakers, especially from neighbouring Asian countries. These findings underscore an imbalance that could influence Japanese students’ perceptions of global English speakers, potentially impacting their identity formation and intercultural competence. This study advocates for a more inclusive approach in textbook development, emphasising the need for representations that reflect English user's global diversity. Such an approach can contribute to a more comprehensive English language education, aligning national identity with global engagement.